Approach to Spanish educational action in Morocco. Students and teachers’ assessment - Dapía Conde, María Dolores; Braña Rey, Fátima (Revista Complutense de Educación, 2021)
Introduction: Spanish-owned centres, where the state teaching of the Spanish education system is taught, are one of the actions that the Spanish government develops abroad, with the greatest presence in Morocco.Method: A descriptive cross-sectional observational design has been chosen, with mixed focus. The data has been collected by submitting a questionnaire to 267 high school students and interviewing four teachers based in Morocco.Results: The profile of the students studying in these centres responds to a young person of Moroccan nationality, who comes from a Spanish educational centre, of Muslim religion, who speaks different languages and middle- or upper-class social class.The schools ‘assessment and the teachings received by students is acceptable. The demand and interest of studies, the approach to Spanish culture and the opportunities for success stand out as more positive aspects. However, they consider that there is no real integration between The Spanish and Moroccan cultural elements, and that the teaching methodology is a bit active and varied.Teachers highlight their mastery of languages and in particular Spanish, their high motivation and assessment of education. They highly value the involvement of families and perceive that both students and families see in these centres an option of socio-labor promotion, which makes it easier for them to leave their country.Discussion/Conclusions: The schools ‘assessment and the teachings received by students is acceptable. The data on the teaching action of this work is consistent with the existence in Morocco of two educational systems that reproduce social inequalities.
Keywords: International education; teaching abroad; secondary education; intercultural education